With the thought of thought: from Abkhazia - Gogoladze, Tamar; Meskhia, Tsiala (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
Three writers, Rene, Geno, and Zaur Kalandia, were born in Abkhazia from a single family. This work focuses on the poetry of René Kalandia (1944-2014). While René Kalandia›s poetic work has been the subject of study in newspaper publications, this article represents the first scientific research on the poet›s work, specifically addressing his connection to Abkhazia. The scientific novelty of this work lies in its attempts to comprehensively examine Kalandia›s unique and profound philosophical poetry. The paper explores various aspects of Kalandia›s work, ranging from deep contemplation to playful wordplay, revealing the individuality of his thinking and his poetic expressions of bohemianism, spiritual yearning, and pagan visions. The harmony between the native surroundings of Abkhazia, the sea, the sky, and its people is eloquently depicted in his poetry, sometimes with confessional undertones and a sense of longing. Reading René›s poetry requires extraordinary energy, talent, and willpower to navigate the emotional storms embedded within. The paradigms presented possess an inexplicable charm and a distinctive enchantment, making it challenging even for professional critics to fully encapsulate. René Kalandia›s poetic rhetoric skillfully combines alienation from the text with intense confessional ntonations, evoking unmanageable traumatic impulses that serve as metaphorical expressions. These impulses give rise to representations of neuroses and formations, bearing metaphorical connotations. Through his poetry, René explores the wonders of the cosmic world, the human soul, dreams, unfulfilled aspirations, and shattered hopes. He embodies the archetype of a lost poet, a sailor navigating the sea of stars, imbued with immense pain and suffering, representing the collective anguish of Georgia. René, who unites the sea and the poet within himself, emerges as a seeker of eternity, possessing unearthly qualities and boundless love. His beautiful poetic masterpieces will forever captivate the interest of future generations, ensuring the continued relevance and resonance of René Kalandia's poetry.